Discharge properties and recruitment of human diaphragmatic motor units during voluntary inspiratory tasks - Butler, J E (Blackwell Science Inc, 1999)
1. The behaviour of inspiratory motoneurones is poorly understood in humans and even for limb muscles there are few studies of motoneurone behaviour under concentric conditions. The current study assessed the discharge properties of the human phrenic motoneurones during a range of non-isometric voluntary contractions. 2. We recorded activity from 60 motor units in the costal diaphragm of four subjects using an intramuscular electrode while subjects performed a set of voluntary inspiratory contractions. These included a range of inspiratory efforts above and below the usual tidal range: breaths of different sizes (5-40% vital capacity, VC) at a constant inspiratory flow (5% VC s(−1)) and breaths of a constant size (20% VC) at different inspiratory flows (2.5-20% VC s(−1)). 3. For all the voluntary tasks, motor units were recruited throughout inspiration. For the various tasks, half-way through inspiration, 61-87% of the sampled motor units had been recruited. 4. When the inspiratory task was deliberately altered, most single motor units began their discharge at a particular volume even when the rate of contraction had altered. 5. The initial firing frequency (median, 6.5 Hz) was consistent for tasks with a constant flow regardless of the size of the breath. However, for breaths of a constant size the initial firing frequencies increased as the inspiratory flow increased (range across tasks, 4.8-9.3 Hz). The ‘final’ firing frequency at the end of inspiration increased significantly above the initial frequency for each task (by 0.8-5.2 Hz) and was higher for those tasks with higher final lung volumes and higher inspiratory flows (range across tasks, 7.8-11.0 Hz). 6. There was no correlation within a task between the time of recruitment and the initial or final firing frequency for each motor unit. However, for each inspiratory task, initial and final firing frequencies were positively correlated. 7. Because the discharge of three to four units could be recorded simultaneously in a range of tasks, a quantitative ‘shuffle’ index was developed to describe changes in their recruitment order. Recruitment order was invariant in the task with the slowest inspiratory flow, but varied slightly, but significantly, in tasks with higher inspiratory flows. 8. The discharge rates of single motor units were compared for targeted voluntary breaths and non-targeted involuntary breaths which were matched for size. There were no significant differences in the initial or final firing frequencies, but recruitment order was not always the same in the two types of breath.